Design, characterization, and clinical evaluation of argan oil nanostructured lipid carriers to improve skin hydration - Tichota, Deise Michele (2021)
Given its advantages in skin application (eg, hydration, antiaging, and protection), argan oil could be used in both dermatological and cosmetic formulations. Therefore, the preparation of nanostructured lipid carriers (NLCs) using argan oil as a liquid lipid is a promising technique, since the former constitute well-established systems for dermal delivery. The aim of this work was to develop a topical formulation of argan oil NLCs to improve skin hydration. Firstly an NLC dispersion was developed and characterized, and afterward an NLC-based hydrogel was prepared. The in vivo evaluation of the suitability of the prepared formulation for the proposed application was assessed in volunteers, by measuring different skin-surface parameters for 1 month. An argan oil NLC-based hydrogel formulation was successfully prepared and characterized. Moreover, the entrapment of the NLCs in the hydrogel net did not affect their colloidal sizes. Additionally, it was observed that this formulation precipitated an increase in skin hydration of healthy volunteers. Therefore, we concluded that the preparation of NLC systems using argan oil as the liquid lipid is a promising strategy, since a synergistic effect on the skin hydration was obtained (ie, NLC occlusion plus argan oil hydration).